Pemberdayaan Ibu Muda Dalam Meningkatkan Keterampilan Pengasuhan Anak Usia Dini Di Kelurahan Lambung Bukit: Empowering Young Mothers Through Parenting Education to Enhance Early Childhood Care in Lambung Bukit, Padang City - Mery Ramadani; Elzi Julia Putri; Firly Malik; Vira Gusti Vanila; Azra Dhabitha Adefyo (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2026)
Early childhood care plays a crucial role in shaping a child's character, health, and future development. In Lambung Bukit Padang City, there are still young mothers who lack knowledge and skills in appropriate parenting, including stimulation of growth and development, nutritional support, and positive behavioral development. This situation can lead to developmental problems in children if left unaddressed. Therefore, this empowerment program is a strategic step to enhance young mothers' capacity through education, training, and mentoring. The goal of this empowerment activity is to increase young mothers' knowledge about healthy, positive, and developmentally stimulating early childhood care patterns. It also trains young mothers' skills in providing balanced nutrition and in stimulating children's motor, cognitive, language, and socio-emotional development. It encourages the creation of a conducive family environment for optimal child growth and development. This activity has four stages: problem analysis, preparation, implementation, and evaluation. The educational component of this program uses presentations, interactive discussions, and the distribution of pocketbooks and leaflets. The results of the T-test indicate a significant difference in mothers' knowledge levels before and after education (p=0.029). The use of various media has been shown to improve mothers' understanding because the material is presented visually and contextually, making it easier to apply in everyday life. Furthermore, mothers should continue to improve their knowledge by establishing peer groups as a learning platform and providing mutual support in early childhood care.